2021
DOI: 10.3390/ijerph18126598
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Geometric Risk Factors Affecting Head-On Collisions through Multiple Logistic Regression: Improving Two-Way Rural Road Design via 2+1 Road Adaptation

Abstract: This study aims to characterize locations on two-way rural roads where head-on crashes are more likely to occur, attending to geometric road design factors. For this purpose, a case-control study was carried out using multiple logistic regression models with variables related to road design parameters, considering several scenarios. The dataset corresponding to cases (places where crashes have occurred) was collected on Spanish “1+1” rural roads over a four-year period. The controls (places where no crashes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…From this table, the highest head-on collision cases occur in two-way rural road traffic systems where vehicles can travel in both directions. A study by Cáceres et al, (2021) and Maksid & Hamsa (2014) identified that head-on collisions are associated with geometric design factors where roads section of 7 meters or wider; road sections with curves; narrowing or drop changes; on wet or snowy roads surfaces; in twilight condition; incorrectly overtaking another vehicle and measurement of medians and paved shoulders not to the correct specification.…”
Section: Category-by-category Line Plot Chartmentioning
confidence: 99%
“…From this table, the highest head-on collision cases occur in two-way rural road traffic systems where vehicles can travel in both directions. A study by Cáceres et al, (2021) and Maksid & Hamsa (2014) identified that head-on collisions are associated with geometric design factors where roads section of 7 meters or wider; road sections with curves; narrowing or drop changes; on wet or snowy roads surfaces; in twilight condition; incorrectly overtaking another vehicle and measurement of medians and paved shoulders not to the correct specification.…”
Section: Category-by-category Line Plot Chartmentioning
confidence: 99%
“…Investigations considering multiple collision modes mainly aim to compare crash frequency, injury severity, and influencing factors of different modes [15,16]. The studies on the single collision mode are mainly concerned with head-on collisions [17]. Multiple pieces of literature conduct separate studies on different collision modes, which can lead to more precise conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…e following human factors, such as the health condition of the driver and pedestrian, alcohol consumption, use of mobile phones while driving, distraction due to roadside advertisements, and the age of the driver, will have a more significant influence on the occurrence of road accidents [5]. Environmental factors associated with the road accidents, such as fog, ice rain, and rain, will have higher relevance to the occurrence of road crashes [16][17][18][19][20]. Accident analysis based on the type of road based on environmental exposure revealed high significance for road accidents in poor weather conditions [6].…”
Section: Introductionmentioning
confidence: 99%